Hope springs eternal : French bondholders and the Soviet repudiation (1915 - 1919) - Kim Oosterlinck; John S. Landon-Lane (Rutgers University, Department of Economics, 2005)
By their extreme nature, repudiations rarely occur. History is therefore crucial to analyze their impact on bond prices. This paper provides an empirical study based on an original database: prices of a Tsarist bond traded in Paris before and after its repudiation by the Soviets. A structural vector autoregression is used to identify shocks to this bond that are orthogonal to shocks hitting a proxy for the Paris bond market, the French 3% rente. French market shocks are thus disentangled from repudiation specific shocks hitting the Russian bond. Consistent with expectations no major Russian shocks appears before the 1917 revolution. For 1918, shocks are mainly related with bailouts or hopes of partial bailouts. In 1919, however, the nature of shocks changes as they can be explained either by the negotiations with the Soviets or by the fate of the White Armies. In view of these elements, we argue that the bonds value were subject to a Peso problem. Their prices essentially reflected expected extreme events that never took place.
Keywords: F34; G1; N24; 330; repudiation; sovereign debt; secession; Russia; Soviet; war; country break-up